2018
DOI: 10.1101/423251
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effects of age at menarche and first sexual intercourse on reproductive and behavioural outcomes: a Mendelian randomization study

Abstract: There is substantial variation in the timing of significant reproductive life events such as menarche and first sexual intercourse. Life history theory explains this variation as an adaptive response to the developmental environment. In environments characterized by harsh conditions, adopting a fast life history strategy may increase fitness. In line with this, there is evidence demonstrating that greater childhood adversity is associated with earlier age at menarche. Here we applied Mendelian randomization (M… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Furthermore, our findings support one study that found little evidence for an association between age at menarche and parity [26]. Additionally, we corroborated the findings of previous MR studies that identified a positive causal relationship between age at menarche and AFB, ALB and age at menopause, and between AFS and ALB [67][68][69].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, our findings support one study that found little evidence for an association between age at menarche and parity [26]. Additionally, we corroborated the findings of previous MR studies that identified a positive causal relationship between age at menarche and AFB, ALB and age at menopause, and between AFS and ALB [67][68][69].…”
Section: Discussionsupporting
confidence: 90%
“…One way of evaluating causality is to use single nucleotide polymorphisms (SNPs) as instrumental variables for the exposure of interest (here age at menarche), under the assumption that the allocation of SNPs at conception is random and unrelated to potential confounding factors [10]. Mendelian randomization has previously been used to explore effects of age at menarche on cardiometabolic traits [9,11,12], depression [13,14], breast cancer [15,16], educational level [17], lung function [18], osteoporosis [19], fracture risk [20], and reproductive/behavioral outcomes [21]. However, these have focused on hypothesized effects by exploring whether associations that have been widely examined in the literature have causal evidence from Mendelian randomization analyses.…”
Section: Introductionmentioning
confidence: 99%
“…(26) Additionally, we corroborated the findings of previous MR studies that identified a positive causal relationship between AAM and AFB, ALB and age at menopause, and between AFS and ALB. (59)(60)(61) Many estimates identified in the primary analysis appear consistent across sensitivity analyses that aim to account for biases. However, some results did not persist in sensitivity analyses checking for robustness to sample overlap and winner's curse.…”
Section: Discussionmentioning
confidence: 74%